2009
DOI: 10.1103/revmodphys.81.299
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-variable optical quantum-state tomography

Abstract: This review covers the latest developments in continuous-variable quantum-state tomography of optical fields and photons, placing a special emphasis on its practical aspects and applications in quantum-information technology. Optical homodyne tomography is reviewed as a method of reconstructing the state of light in a given optical mode. A range of relevant practical topics is discussed, such as state-reconstruction algorithms ͑with emphasis on the maximum-likelihood technique͒, the technology of time-domain h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
1,140
2
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 984 publications
(1,164 citation statements)
references
References 235 publications
(260 reference statements)
11
1,140
2
11
Order By: Relevance
“…Repeating this process many times and obtaining the marginals for a large number of mechanical phase-space angles θ is sufficient to uniquely determine the mechanical quantum state of motion [35]. Quantum state tomography by measurement of the marginals was first realized with optical fields using homodyne interferometry [36] and has now become an indispensable tool in the field of quantum optics [37] being applied to other physical systems such as molecular vibration [38], spin ensembles [39], and microwave fields [40]. Here we implement such mechanical state tomography by utilizing the pulsed measurement outcome probability distribution…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Repeating this process many times and obtaining the marginals for a large number of mechanical phase-space angles θ is sufficient to uniquely determine the mechanical quantum state of motion [35]. Quantum state tomography by measurement of the marginals was first realized with optical fields using homodyne interferometry [36] and has now become an indispensable tool in the field of quantum optics [37] being applied to other physical systems such as molecular vibration [38], spin ensembles [39], and microwave fields [40]. Here we implement such mechanical state tomography by utilizing the pulsed measurement outcome probability distribution…”
Section: Experimental Protocolmentioning
confidence: 99%
“…An exhaustive review of continuous variable entanglement theory can be found in a number of specialized reviews (Kok et al, 2007;Lvovsky and Raymer, 2009). Here, we briefly introduce some important quantities of entangled photon pairs, in order to later distinguish genuine entanglement from other bandwidth properties, which could also be encountered with classical light sources.…”
Section: Photon Entanglement In Multimode Statesmentioning
confidence: 99%
“…Entangled photons have become an invaluable resource in quantum optics with possible applications to cryptography [1], lithography [2], metrology [3] and quantum computing [4,5]. Applications to spectroscopy received considerable attention in experiments [6][7][8][9] as well as in theoretical works [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%